Sudden and the gradual - Approaches to Enlightenment in Chinese thought - Venkatakrisnna, B V (Journal of Dharma, 1992)
Peter N Gregory, Sudden and the gradual - Approaches to Enlightenment in ChineE thought. Delhi: Motilal Banarasidas, 1991, Pp. 474.